2017
DOI: 10.22219/sm.v8i1.4091
|View full text |Cite
|
Sign up to set email alerts
|

EFEK EKSTRAK DAUN SIRIH MERAH (PIPER CROCATUM RUIZ & PAV) TERHADAP PERTUMBUHAN (STREPTOCOCCUS PNEUMONIAE)

Abstract: Efek Ekstrak Daun Sirih Merah (Piper crocatum Ruiz & Pav) Terhadap Pertumbuhan (Streptococcus pneumoniae). Latar belakang: Perkembangan resistensi Streptococcus pneumonia terhadap obat antimikroba merupakan masalah potensial sehingga untuk pengobatannya diperlukan alternatif lain. Daun sirih merah diduga mempunyai manfaat sebagai antimikroba karena mengandung flavonoid, minyak atsiri, tanin, dan alkaloid yang bekerja dengan cara merusak membran sel dan dinding sel bakteri. Tujuan: Untuk mengetahui pengaruh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Research conducted by (Wicaksono et al 2009) showed that the methanol extract of red betel leaf has a cytotoxic effect with an IC 50 value of 50% and has the potential to inhibit the proliferation of T47D breast cancer cells. Red betel leaf extract inhibited the growth of HeLa cells by 86% by the MTT method (Suci 2014). Based on the results obtained, both extracts and fractions of red betel leaf showed fluctuating results between concentration and inhibition percentage, this is presumably because the content of bioactive compounds contained in red betel leaf is still diverse and the levels of compounds contained at various concentrations are still different.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Research conducted by (Wicaksono et al 2009) showed that the methanol extract of red betel leaf has a cytotoxic effect with an IC 50 value of 50% and has the potential to inhibit the proliferation of T47D breast cancer cells. Red betel leaf extract inhibited the growth of HeLa cells by 86% by the MTT method (Suci 2014). Based on the results obtained, both extracts and fractions of red betel leaf showed fluctuating results between concentration and inhibition percentage, this is presumably because the content of bioactive compounds contained in red betel leaf is still diverse and the levels of compounds contained at various concentrations are still different.…”
Section: Discussionmentioning
confidence: 94%
“…Red betel (Piper crocatum Ruiz and Pav) is a popular traditional herbal plant in Asia commonly referred to as the Golden Heart of Nature. Based on previous studies in vitro, the best anticancer potential was found in red betel leaf simplicia which had the highest inhibitory activity of 85.72% in HeLa cells with a concentration of 800 ppm (Suci 2014). Ethanol extract and ethyl acetate fraction of red betel leaf showed the best inhibition results at a concentration of 500 ppm, which was 98.18±1.21% in colon cancer (Umar 2022).…”
Section: Journal Of Biosciences Journal Of Biosciencesmentioning
confidence: 94%
“…7,11 Other factors that influence the results of the study are biological factors including plant species, location of harvest, time of harvest, storage of plant material, age of plants and parts used. 14 The location of growth is related to the height of the growing site which is strongly influenced by local climatic conditions. Besides, the age of the plant also affects the content of xanthorrhizol which is an active compound in the temulawak rhizome.…”
Section: Discussionmentioning
confidence: 99%